ADP-induced platelet reactivity and bleeding events in patients with acute myocardial infarction complicated by cardiogenic shock. (26th April 2021) - Scherer, C; Luesebrink, E; Massberg, S; Sibbing, D; Orban, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: While previous reports showed ADP-induced platelet reactivity to be an independent predictor of bleeding after PCI in stable patients, this has never been investigated in patients with cardiogenic shock (CS). Methods: The association of bleeding events with respect to ADP-induced platelet aggregation was investigated in patients undergoing primary PCI for acute myocardial infarction complicated by cardiogenic shock (AMI-CS) and with available on-treatment ADP-induced platelet aggregation measurements. Results: Out of 233 patients, 74 suffered from a severe BARC 3 or higher bleed. ADP-induced platelet aggregation was significantly lower in patients with BARC≥3 bleedings (10 AU [IQR 3 - 13] vs. 15 AU [IQR 9 - 25], p < 0.001). Multivariate analysis identified on-treatment ADP-induced platelet aggregation as an independent risk factor for bleeding (HR = 0.968 per AU, 95% confidence interval (CI) 0.942-0.994). An optimal cut-off value of <12 AU for ADP-induced platelet aggregation to predict BARC≥3 bleedings was identified via ROC analysis. Moreover, use of VA-ECMO (HR 1.972, 95% CI 1.003-3.879) or coaxial left ventricular pump (HR 2.593, 95% CI 1.509-4.455), first lactate (HR 1.093 per mmol/l, 95% CI 1.037-1.152) and thrombocyte count (HR 0.994 per G/l, 95% CI 0.990-0.998) were independent predictors of BARC≥3 bleedings. There was no significant difference in survival nor ischemic events between patients with low and high on-treatment platelet reactivity. Conclusion: Lower on-treatment ADP-induced platelet aggregation was independently associated with severe bleeding events in patients with AMI-CS. The value of platelet function testing for bleeding risk prediction and guidance of anti-thrombotic treatment in CS warrants further investigation.